Transmission and mortality risk assessment of severe fever with thrombocytopenia syndrome in China: results from 11-years' study - Qiulan Chen; Dong Yang; Yanping Zhang; Mantong Zhu; Ning Chen; Zainawudong Yushan (BMC, 2022)
Abstract Background The transmission and fatal risk of severe fever with thrombocytopenia syndrome (SFTS), an emerging infectious disease first discovered in China in 2009, still needed further quantification. This research aimed to analyze the SFTS clusters and assess the transmission and mortality risk for SFTS. Methods Both epidemiological investigation and case reports regarding SFTS clusters in China during 2011-2021 were obtained from the Public Health Emergency Information Management System of the Chinese Center for Disease Control and Prevention Information System. The transmission risk was evaluated by using the secondary attack rate (SAR) and relative risk (RR). Mortality risk factors were analyzed using a logistic regression model. Results There were 35 SFTS clusters during 2011-2021 involving 118 patients with a fatality rate of 22.0%. The number of clusters annually increased seasonally from April to September. The clusters mainly occurred in Anhui (16 clusters) and Shandong provinces (8 clusters). The SAR through contact with blood or bloody fluids was much higher than that through contact with non-bloody fluids (50.6% vs 3.0%; χ 2  = 210.97, P < 0.05), with an RR of 16.61 [95% confidence interval (CI): 10.23-26.97]. There was a statistically significant difference in the SAR between exposure to the blood of a deceased person during burial preparation and exposure to the living patients' blood (66.7% vs 34.5%; χ 2  = 6.40, P < 0.05), with an RR of 1.93 (95% CI: 1.11-3.37). The mortality risk factors were a long interval from onset to diagnosis [odds ratio (OR) = 1.385), 95% CI: 1.083-1.772, P = 0.009) and advanced age (OR: 1.095, 95% CI: 1.031-1.163, P = 0.01). Conclusions The SFTS clusters showed a high mortality rate and resulted in a high SAR. Contact with a bleeding corpse was associated with a higher infection risk, compared with contacting the blood from living patients. It is important to promote early detection and appropriate case management of patients with SFTS, as well as improved handling of their corpses, to prevent further transmission and mortality. Graphical abstract